Pharmacokinetic Investigation to Study the In Vivo Bioavailability of Thiolated Chitosan Based Repaglinide Buccal Tablets - Raja Navamanisubramanian; Raghunandan Nerella; Shanmuganathan Seetharaman (Tabriz University of Medical Sciences, 2020)
Background: Repaglinide (REP) is an antihyperglycemic drug having low bioavailability due to its extensive first-pass metabolism. The present study aimed to develop and pharmacokinetic investigte the thiolated chitosan (TC) based buccal tablets of REP for improved bioavailability. Methods: TC was prepared by conjugation of L-cysteine with chitosan. The amount of free thiol groups present in TC was determined by UV-spectrophotometry using Ellman's reagent. TC based REP buccal tablets were prepared by two layers co-compression method and characterized for in vitro and ex vivo parameters. The in vivo performance of prepared REP buccal tablets was assessed by the pharmacokinetic study in New Zealand white rabbits. Results: The prepared TC resulted in 87%w/w yield with 52.3±3.2 μM free thiol functional groups per 10 mg of TC. The prepared formulations have good flow nature and compressibility, acceptable thickness (2.02 to 2.1 mm), weight (60.11 to 61.06 mg), surface pH (6.59 to 6.81) and drug content (98.92 to 101.08 %w/w). The presence of TC significantly improved the mucoadhesion strength, sustained the in vitro release and enhanced the ex vivo permeation of REP buccal tablets. The shelf life of REP buccal tablets was found to be 15.07 months in accelerated storage conditions. The prepared REP buccal tablets (V5) have area under the curve (712.22±15.91 ng/mL/h) and mean residence time (4.66±0.25 h) was 1.89 and 1.83 folds higher than oral bolus respectively. Conclusion: TC based REP buccal tablets are capable of controlled transbuccal release of REP for a prolonged time and have better bioavailability than oral bolus.